Study of Management Information Systems on Employee Performance Through Interpersonal Communication at Regional State Intelligence Agency Offices South Sulawesi Province - Dwi Surjatmodjo (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
Management Information System is a planning system within agencies that involves internal control such as the use of resources, documents, technology, and interpersonal communication as one of the strategies in the organization. This research uses systematic review to review reviews of clearly formulated questions that use systematic and explicit methods to identify, select, and critically evaluate relevant research, and to collect and analyze data from the studies included in the review. Data obtained from 54 references that are relevant to the study of management information systems. The results of the research above, it appears that the Information Quality Factor for the Management Information System is still not optimal with the demands needed to improve employee interpersonal communication at the Regional State Intelligence Agency Office of South Sulawesi Province, and the Communication Factor is very significant for improving employee performance.